Design, optimization, and ADMET evaluation of S11a-0000168202: A promising LIMK1 inhibitor for gastric cancer treatment - Guojun Li; Jionghuang Chen; Rui Chen; Weihua Yu (PLoS ONE, 2025)
This study focuses on the development and optimization of S11a-0000168202, a novel LIMK1 inhibitor with potential therapeutic applications in gastric cancer. Through scaffold hopping and structural modification of HIT100844099, S11a-0000168202 demonstrated enhanced binding stability and stronger interactions with key LIMK1 residues, including GLU-414, ILE-416, and HIS-464. Molecular dynamics simulations and MMGBSA analyses confirmed the compound’s stability, while ADMET evaluation revealed favorable properties such as moderate lipophilicity, good human intestinal absorption, and low P-glycoprotein inhibition. Despite the promising computational results, the lack of experimental validation remains a limitation. Future studies should focus on in vitro and in vivo testing to confirm S11a-0000168202’s efficacy, pharmacokinetics, and safety. This compound holds significant potential as a therapeutic agent for LIMK1-targeted gastric cancer treatment.